You won’t believe what we found out about online news! : Clickbaiting and the influence on brand trust in online news media - Grandin, Ruben; Forsberg, Eric (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
The internet is changing the game for traditional print media, newspapers are now forced to move onto the web. The adjustment from print to the web has created a highly competitive market for most news brands. The increasing amount of information online which is constantly being pushed on the consumer’s from way too many different sources is creatinga different atmosphere for journalists. The need to stay competitive is generating new strategies for the online news brands trying to stay relevant. A new growing phenomenon in this atmosphere is called clickbaiting, which is best described by an exaggerated headline with little or no connection to the content that the article actually leads too. Focusing on the number of clicks the articles can get, instead of satisfying the consumers need. A gap in literature was identified between building long lasting trust relationship and the current online news media market. This study aim to find the most important factors that influence the consumers trust for clickbaiting online news brands. This was done through an exploration of the influential factors of online brand trust where six underlying factors of online brand trust was identified. Quantitative data was collected through an online survey, asking students of Luleå University of Technology their thoughts about trust in clickbaiting online news sites. A total of 197 full answers were collected and then analyzed through the use of statistical techniques. The conclusions from the data analysis suggested that a combination of the underlying factors brand reputation and good online experience was the most influential for explaining online brand trust. Implying that in practice, a consumer is likely to have a high trust for a clickbaiting news site that consistently provide a positive experience for the consumer, while still keeping up an image of being a reputable news site.